2022
DOI: 10.1186/s40634-022-00497-5
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of total cold-water immersion's effects to ice massage on recovery from exercise-induced muscle damage

Abstract: Purpose The purpose of the study is to compare the effects of total cold-water immersion to ice massage on muscle damage, performance, and delayed onset of muscle soreness. Methods Sixty participants were randomized into two groups where they completed a muscle damage protocol. Afterward, muscle damage, muscle performance, and delayed onset muscle soreness were respectively measured by serum Creatine Kinase (CK) test, one-repetition maximum (1-RM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Additionally, we observed the effects of probiotic supplementation on mitigating EIMD and enhancing recovery. Research shows that muscle strength typically decreases within 24 to 48 h post-exercise and gradually returns to baseline after about 72 h [ 69 , 70 ]. Our results demonstrated that supplementation with PL-02, LY-66, and PL-02+LY-66 mitigated reductions in RPF and pRFD post-exercise, while also accelerating recovery of these parameters, thus supporting muscle protection and efficient recovery after physical exertion.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we observed the effects of probiotic supplementation on mitigating EIMD and enhancing recovery. Research shows that muscle strength typically decreases within 24 to 48 h post-exercise and gradually returns to baseline after about 72 h [ 69 , 70 ]. Our results demonstrated that supplementation with PL-02, LY-66, and PL-02+LY-66 mitigated reductions in RPF and pRFD post-exercise, while also accelerating recovery of these parameters, thus supporting muscle protection and efficient recovery after physical exertion.…”
Section: Discussionmentioning
confidence: 99%
“…The application of post-exercise ice therapy can reduce tissue temperature and blood flow, thereby alleviating cardiovascular stress, eliminating muscle metabolic by-products, reducing exercise-induced symptoms, and accelerating post-exercise recovery [28]. Numerous studies have shown that ice therapy can effectively relieve DOMS at 24 h after exercise [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The power of the hips in the swing stage of jogging is mainly based on the movement and interaction torque. 10 The muscles around the buttocks are always in the opposite direction of the interaction torque during movement. The ankle is less torqued than the hip and knee joints.…”
Section: Discussionmentioning
confidence: 99%